Oil Sketches of the XIXth and XXth Centuries. - Patrick Derom Gallery, Brussel; Geerinckx, Brigitte (Brussel : Patrick Derom Gallery, 1999)
Agneessens, Edouard ; Bordes, Ernest ; Brangwyn, Frank ; Carolus-Duran, Charles ; Chevalier, Ferdinand ; Cluysenaar, Alfred ; Cross, Henri-Edmond ; De Cock, Cesar ; Diaz de la Pena, Narcisse Virgie ; Evenepoel, Henri ; Gigoux, Jean-François ; Jacobs, Jacob ; Jefferys, Marcel ; Khnopff, Fernand ; Klinger, Max ; Lies, Joseph ; Mednyanszky, László ; Menard, Emile Rene ; Meunier, Constantin ; Regnault, Henri Alexandre Georges ; Rops, Félicien ; Smeers, Frans ; Thivier, Emile-Louis ; Van Moer, Jean-Baptiste ; Wauters, Emile
biografie
Oil Sketches of the XIXth and XXth Centures, Patrick Derom Gallery, Brussel, autumn 1999
Engels
boek
Keywords: 19de eeuw; 20ste eeuw